1990
DOI: 10.1152/ajpgi.1990.259.5.g720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calcium and magnesium absorption: in vivo and in vitro studies

Abstract: Transport characteristics of Ca and Mg were compared at three different levels of the absorptive process in male (120-170 g) Wistar rats. Balance studies in intact rats revealed that fractional Ca absorption decreased with increased Ca intake so that net Ca absorption remained constant. Fractional Mg absorption decreased modestly with increased Mg intake so that net Mg absorption increased proportionately with increased dietary Mg. Everted duodenal sacs demonstrated the presence of active Ca absorption with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In spite of this, the intestine seems to have a limited role in regulation of the Mg 2Ï© balance. In contrast to other minerals, intestinal Mg 2Ï© absorption is poorly regulated and depends mainly on Mg 2Ï© intake (216,461). Thus the kidneys presumably primarily regulate the maintainance of Mg 2Ï© homeostasis.…”
Section: A Magnesium In Intestinementioning
confidence: 99%
“…In spite of this, the intestine seems to have a limited role in regulation of the Mg 2Ï© balance. In contrast to other minerals, intestinal Mg 2Ï© absorption is poorly regulated and depends mainly on Mg 2Ï© intake (216,461). Thus the kidneys presumably primarily regulate the maintainance of Mg 2Ï© homeostasis.…”
Section: A Magnesium In Intestinementioning
confidence: 99%
“…With a daily intake of 370 mg, the absorption rate of Mg 2+ in the intestine ranges from 30-50% [ 13 ]. However, the efficiency of Mg 2+ uptake is dependent on the ingested dose [ 15 , 16 ]. For example, early studies with a low dietary Mg 2+ intake showed that the relative absorption rate can reach 80% [ 17 ], whereas it is reduced to 20% with Mg 2+ surfeits [ 18 ].…”
Section: Mechanisms Of Mg2+ Absorption In the Intestinementioning
confidence: 99%
“…In the present experiment the highest plasma 25Mg enrichment was observed at about 4 h reaching 84 % and 144 % in rats receiving 6 or 12 mg 25Mg respectively. Others have also observed a peak of 28Mg 4 h after isotope administration in rats (Aikawa, 1981;Hardwick et al 1990b). The plasma and urine enrichment levels at 24 h (35 %, 54 %) and at 72 h (15 %, 20 %) respectively were sufficiently high to permit accurate isotopic measurements and their use to calculate several kinetic constants of Mg metabolism, particular1 if used in conjunction with intravenous administration of a second Mg stable isotope ( Mg) as in the next experiment.…”
Section: Single Labelling and Metabolic Balance Studymentioning
confidence: 95%